Research Progress on the Digestion Characteristics and Influencing Factors of Whole Grain Brown Rice - WANG Dan; ZHAI Xiao-tong; ZHANG Na; WU Na-na; TAN Bin (Liang you shipin ke-ji)
The development of the whole grain industry in China is a key measure in implementing the “Food Security Guarante Law” strategy and the “Healthy China” strategy. It also aligns with practicing the broader concept of food security. Rice is a staple food for Chinese residents, and substituting white rice with brown rice is an effective way to increase whole grains intake. Studies have shown that whole grain brown rice provides health benefits in blood glucose and lipid regulation, as well as weight control. These effects attributed to the effects of dietary fiber, various micronutrients, and bioactive compounds abundant in brown rice. Additionally, these health effects also result from alterations in the digestion and absorption efficiency of dietary nutrients like carbohydrates and proteins, mediated by these bioactive compounds. The digestion process of food is a key link related to the aforementioned effects. Current research methods for characterizing the digestion process of brown rice mainly static and dynamic in vitro static simulations, as well as in vivo digestion. This article systematically reviews the macro and micronutrient components and bioactive substances of rice. It also explores the effects of different processing accuracy and brown rice processing techniques on rice starch digestion characteristics and their potential mechanisms. The aim is to provide reference for the development and selection of processing technologies for whole grain brown rice.